Onion Peel Ethylacetate Fraction and Its Derived Constituent Quercetin 4′-O-β-D Glucopyranoside Attenuates Quorum Sensing Regulated Virulence and Biofilm Formation - Al-Yousef, Hanan M.; Ahmed, Atallah F.; Al-Shabib, Nasser A.; Laeeq, Sameen; Khan, Rais A.; Rehman, Md T.; Alsalme, Ali; Al-Ajmi, Mohamed F.; Khan, Mohammad S.; Husain, Fohad M. (Frontiers in Microbiology, 2017)
The resistance and pathogenesis of bacteria could be related to their ability to sense and respond to population density, termed quorum sensing (QS). Inhibition of the QS system is considered as a novel strategy for the development of antipathogenic agents, especially for combating drug-resistant bacterial infections. In the present study, the anti-QS activity of Onion peel ethylacetate fraction (ONE) was tested against Chromobacterium violaceum CV12472 and Pseudomonas aeruginosa PAO1. ONE inhibit the QS-mediated virulence factors production such as violacein in C. violaceum and elastase, pyocyanin in P. aeruginosa. Further, the treatment with sub-MICs of ONE significantly inhibited the QS-mediated biofilm formation, EPS (Extracellular polymeric substances) production and swarming motility. Further, quercetin 4′-O-β-D glucopyranoside (QGP) was isolated from ONE and its anti-QS potential was confirmed after observing significant inhibition of QS-controlled virulence factors such as violacein, elastase, pyocyanin and biofilm formation in test pathogens. Molecular docking analysis predicted that QGP should be able to bind at the active sites of Vfr and LasR, and if so blocks the entry of active sites in Vfr and LasR.